Internal Herniation Through a Defect in the Broad Ligament of the Uterus - Hsin-Fen Lu (Elsevier, 2005)
Objective: Intestinal obstruction caused by internal herniation of the bowel at a tear in the uterine broad ligament is extremely rare. Accurate preoperative diagnosis is very difficult. Here, we present a case with internal herniation through a defect in the broad ligament of the uterus. Case Report: A 41-year-old female complained of colicky pain over the lower abdomen, nausea, and vomiting for 2 days. No significant history except cesarean section was given. Transvaginal ultrasound revealed a cystic structure with peristalsis located at the broad ligament of the uterus. Highly suspicious of bowel obstruction, we performed an emergency laparoscopy and discovered intestinal herniation at a broad ligament tear. The herniated bowel loop was reduced and the tear was sutured primarily. The reduced bowel loop was viable with no evidence of gangrene or perforation. The patient recovered uneventfully. Conclusion: Good prognosis relies on early surgical correction before bowel gangrene or perforation of the strangulated bowel, especially in patients with previous gynecologic or obstetric surgery. Transvaginal ultrasound by an experienced operator may be helpful for this diagnosis.